Measurement and meaning of markers of reactive species of oxygen, nitrogen and sulfur in healthy human subjects and patients with inflammatory joint disease. (21st September 2011) - Winyard, Paul G.; Ryan, Brent; Eggleton, Paul; Nissim, Ahuva; Taylor, Emma; Lo Faro, Maria Letizia; Burkholz, Torsten; Szabó-Taylor, Katalin E.; Fox, Bridget; Viner, Nick; Haigh, Richard C.; Benjamin, Nigel; et al.
Abstract : Reactive species of oxygen, nitrogen and sulfur play cell signalling roles in human health, e.g. recent studies have shown that increased dietary nitrate, which is a source of RNS (reactive nitrogen species), lowers resting blood pressure and the oxygen cost of exercise. In such studies, plasma nitrite and nitrate are readily determined by chemiluminescence. At sites of inflammation, such as the joints of RA (rheumatoid arthritis) patients, the generation of ROS (reactive oxygen species) and RNS overwhelms antioxidant defences and one consequence is oxidative/nitrative damage to proteins. For example, in the inflamed joint, increased RNS-mediated protein damage has been detected in the form of a biomarker, 3-nitrotyrosine, by immunohistochemistry, Western blotting, ELISAs and MS. In addition to NO, another cell-signalling gas produced in the inflamed joint is H2 S (hydrogen sulfide), an RSS (reactive sulfur species). This gas is generated by inflammatory induction of H2 S-synthesizing enzymes. Using zinc-trap spectrophotometry, we detected high (micromolar) concentrations of H2 S in RA synovial fluid and levels correlated with clinical scores of inflammation and disease activity. What might be the consequences of the inflammatory generation of reactive species? Effects on inflammatory cell-signalling pathways certainly appear to be crucial, but in the current review we highlight the concept that ROS/RNS-mediated protein damage creates neoepitopes, resulting in autoantibody formation against proteins, e.g. type-II collagen and the complement component, C1q. These autoantibodies have been detected in inflammatory autoimmune diseases.